There is much to be learnt about the costs of multiple sclerosis in Latin America - Marina Romano; Gerardo Machnicki; Juan Ignacio Rojas; Nadina Frider; Jorge Correale (Arquivos de Neuro-Psiquiatria)
METHOD: A systematic review of the literature from 1990 to 2011 was conducted. Outcome measures included: mean cost of disease modifying therapies (DMTs), mean cost of treatment of relapses and mean cost of disease by stage stratification measured by the expanded disability status scale (EDSS). RESULTS: Seven studies from three countries (Brazil, Argentina and Colombia) were included. In 2004, in Argentina, the mean cost of DMT treatment was reported to be USD 35,000 per patient treated. In Brazil, the total MS expenditure of DMTs rose from USD 14,011,700 in 2006 to USD 122,575,000 in 2009. Patient costs ranged between USD 10,543 (EDSS 8-9.5) and USD 25,713 (EDSS 3-5.5). Indirect costs markedly increased for the EDSS 8-9.5 patients. CONCLUSION: Further research assessing the economic burden of MS in LA is warranted.